Assessment of genetic diversity of garden pea (Pisum sativum) as perspective to isolate horticulturally desirable transgressive segregants - SHARMA, AKHILESH; BHARDWAJ, AJAY; KATOCH, VIVEKA; SHARMA, JAIDEV (The Indian Journal of Agricultural Sciences, 2026)
Genetic restructuring of germplasm is essential to identify the potential genotypes for use in future breeding programmes. An attempt was made to determine the degree of divergence among 41 diverse genotypes of garden pea (Pisum sativum) (23 isolated from induced mutations, 12 through hybridization followed by selection and six other released varieties) by following multivariate analysis. These genotypes were evaluated in Randomized Complete Block Design with three replications in winter season during 2009-10 and 2010-11. A considerable genetic diversity was observed and the genotypes were arranged into 8, 13 and 5 clusters in 2009-10, 2010-11 and pooled over years, respectively with maximum genotypes in cluster I. DPPMR-09-1, DPP-25G and DPPM 64 exhibited consistency in clustering pattern over the years. Harvest index, total biomass and 100-seed weight contributed maximum towards total genetic divergence. To conclude, genotypes Punjab 89, DPPM 74, Palam Priya, DPPM 64, DPPM 73, DPPMFWR 4, DPPMFWR 30-2 and DPP 25G offer promise as a breeding stock for utilization in hybridization as parents for the isolation of transgressive segregants in garden pea.